2020
DOI: 10.5334/jime.549
|View full text |Cite
|
Sign up to set email alerts
|

Textbook Broke: Textbook Affordability as a Social Justice Issue

Abstract: In light of rising textbook prices, open education resources (OER) have been shown to decrease non-tuition costs, while simultaneously increasing academic access, student performance, and time-to-graduation rates. Yet very little research to date has explored OER's specific impact on those who are presumed to benefit most from this potential: historically underserved students. This reality has left a significant gap of understanding in the current body of literature, resulting in calls for more empirically-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 32 publications
1
59
0
1
Order By: Relevance
“…A survey conducted at the end of the first semester of UPIKE's initiative indicated that nearly 62% of students felt that having free textbooks increased their engagement with course materials and over 65% believed it improved their performance in class (an additional 16.2% and 20.6% respectively were neutral). Students indicated that the initiative not only relieved stress, but made it easier to access materials, which they viewed as a social justice issue, echoing research by Jenkins et al (2020). There were a few areas where students ran into difficulty.…”
Section: Discussionmentioning
confidence: 94%
“…A survey conducted at the end of the first semester of UPIKE's initiative indicated that nearly 62% of students felt that having free textbooks increased their engagement with course materials and over 65% believed it improved their performance in class (an additional 16.2% and 20.6% respectively were neutral). Students indicated that the initiative not only relieved stress, but made it easier to access materials, which they viewed as a social justice issue, echoing research by Jenkins et al (2020). There were a few areas where students ran into difficulty.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have shown that the majority of faculty believe textbook costs are too high and that this is a significant concern for students (Jaschik & Lederman 2018;Seaman & Seaman 2019). Commercially available textbooks have also been shown in multiple environments to cause stress and result in students failing to purchase or delaying purchasing materials necessary to be successful (Jenkins et al 2020;Jhangiani & Jhangiani 2017;Martin et al 2017;Murphy & Rose 2018). The impact on students is often personal as well as academic.…”
Section: Access Barriers Related To Textbook Costs Financial and Psychological Impact On Studentsmentioning
confidence: 99%
“…While the high cost of commercial textbooks was burdensome for higher education students prior to the pandemic (Jenkins et al 2020 ), the impacts of such costs in the challenging environment that students face today are magnified. A survey that gathered data in April–May 2020 in the United States for instance, found that nearly 60% of around 38,000 student respondents faced food insecurity, housing insecurity, and homelessness (Goldrick-Rab et al 2020 ).…”
Section: What Is the Value Of Oer For Inclusion And Equity?mentioning
confidence: 99%
“…Significantly, these issues have disproportionate impacts on certain student populations, which is one of the reasons that Lambert ( 2018 ) encourages researchers and practitioners to view open education, OER, and openness as social justice issues. Low-income students, students of color, and historically underserved students in general may feel the hardships of high textbook prices more than others (e.g., Jenkins et al 2020 ). When Goldrick-Rab et al, ( 2020 ) find a gap of 19% in basic needs insecurity between students identifying as White or Caucasian and students identifying as Black or African American, and Frenette et al ( 2020 ) show that over the next 5 years they expect the pandemic to lead to greater potential financial losses for women than men post-secondary graduates in Canada, it becomes clear that the impacts of high textbook prices will continue having greater impacts on some students more than others.…”
Section: What Is the Value Of Oer For Inclusion And Equity?mentioning
confidence: 99%